Gestión del control de inventario en la empresa Lopatrucks. S.A. - Aray Vera, Colombia Yaneysi (2021)
LOPATRUCKS SA is a company that is entirely dedicated to the wholesale and retail of cleaning products, lubricants, filters and refrigerants for the maintenance of automotive vehicles, this company had its beginnings simply being a car washer and that currently has been expanded by opening new doors in the labor market, it has a branch on E25 via Babahoyo, its headquarters located in Ángel Burgos and 28 de Mayo streets and a complete interface of services made available to the client to keep their vehicles impeccable. At present, companies that are dedicated to the distribution of products show a great need to update and innovate the way of keeping control of their inventories, basically they do it first to avoid losses in the short, medium and long term and second to meet the customer's need in an efficient way and always want to come back. Let us also remember that not having a correct control of the stock of your inventory causes a significant decrease in your profits. This work is mainly about determining if the inventory system that is currently being used in the company is adequate or not.